The effectiveness of combining ultrasound therapy with splinting and exercise therapy for patients with carpal tunnel syndrome - Sayu Aryantari Putri Thanaya; Putu Ayu Sita Saraswati; Made Donna Safira Pitaloka Barani (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Carpal tunnel syndrome (CTS) can cause patients to experience negative symptoms that can significantly affect their ability to use their hands to perform daily activities. This study aimed to compare the effectiveness of a combination of splinting and exercise therapy with or without ultrasound therapy in improving CTS symptoms and the functional status of patients. Methods: This randomized pre and post-test control group design study was conducted in private physiotherapy practices in the Denpasar area from August to September 2022. Twenty-four subjects with unilateral CTS were randomly divided into an Intervention Group (n=12; splinting, exercise therapy, and ultrasound therapy) and a Control Group (n=12; splinting and exercise therapy only). Splinting was used all day and night for four weeks. Exercise therapy was given three times per week for four weeks. Ultrasound therapy was given once a day, three times per week, for four weeks. The subject's symptoms and functional status before and after treatment were evaluated using the Boston Carpal Tunnel Syndrome Questionnaire (BCTSQ), which consists of the Symptom Severity Scale (SSS) and the Functional Status Scale (FSS). Results: Significant improvements were found in SSS and FSS in Group 1 (SSS: p=0.000; FSS: p=0.000) and Group 2 (SSS: p=0.000; FSS: p=0.000), and a significant between-group difference was found in SSS (p=0.000) and FSS (p=0.001). Conclusion: The addition of ultrasound therapy to splinting and exercise therapy is more effective than that in improving the symptoms and functional status of patients with CTS.